Etika Profesi Hakim dalam Perspektif Peradilan Islam - Abdullah Al Ghifari (UNISBA Press, 2022)
Abstract. To create a Supreme Indonesian judiciary, the Supreme Court and Juducial Commission of the Republic of Indonesia have developed a code of ethics and guidelines for judges' behavior, but according to ICW's records, there are still 20 judges involved in corruption cases. In Islamic courts, the code of ethics for the judge's profession is based on the understanding of the Qur'an and hadith which aims to create a decent and moral society. The purpose of this study is to find out how the professional code of ethics of judges in Indonesia and according to Islamic courts, then whether the professional ethics of Indonesian judges is in line with the professional ethics of judges according to Islamic courts. This research is a normative legal research, through a normative juridical approach. The type of this research is the library research method sourced from the Qur'an, Hadith, laws and regulations and various references such as books and journals. The data collection technique in this research is the data collection method which is a documentation study, and the data analysis in this study is qualitative analysis. high integrity, responsible, upholding self-esteem, high discipline, humble and professional. In Islamic justice there are four basic values ​​that build judge ethics, namely righteousness, justice, free will, and responsibility. So basically the code of ethics for the profession of judges in Indonesia is in line with the code of ethics for the profession of judges according to Islamic courts. Abstrak. Untuk mewujudkan badan peradilan Indonesia yang Agung, MA dan KY Republik Indonesia membuat kode etik dan pedoman perilaku hakim, namun menurut catatan ICW, masih ada 20 hakim yang tersangkut kasus korupsi. Di dalam peradilan Islam, kode etik profesi hakim ini berlandaskan dari pemahaman Al-Qur’an dan hadits yang bertujuan untuk mewujudkan masyarakat yang layak dan bermoral. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana kode etik profesi hakim di Indonesia dan menurut peradilan Islam, kemudian apakah etika profesi hakim Indonesia sudah sejalan dengan etika profesi hakim menurut peradilan Islam. Penelitian ini merupakan penelitian hukum normatif, melalui pendekatan yuridis normatif. Jenis dari penelitian ini ialah dengan metode riset kepustakaan yang bersumber dari Al-Qur’an, Hadits, peraturan perundang-undangan serta berbagai referensi seperti buku dan jurnal. Teknik pengumpulan data pada penelitian ini ialah dengan metode pengumpulan data yang bersifat studi dokumentasi, dan Analisis data dalam penelitian ini yaitu dengan analisis kualitatif. Kesimpulannya yaitu kode etik profesi hakim Indonesia memuat sepuluh prinsip, yaitu berperilaku adil, jujur, arif dan bijaksana, mandiri, berintegritas tinggi, bertanggung jawab, menjungjung tinggi harga diri, berdisiplin tinggi, rendah hati dan profesional. Dalam peradilan Islam terdapat empat nilai dasar yang membangun etika hakim, yaitu kebeneran, keadilan, kehendak bebas, dan pertanggung jawaban. Sehingga pada dasarnya kode etik profesi hakim Indonesia ini sejalan dengan kode etik profesi hakim menurut peradilan Islam.